2016
DOI: 10.1590/0004-282x20160009
|View full text |Cite
|
Sign up to set email alerts
|

Main determinants of physical activity levels in individuals with Parkinson’s disease

Abstract: This study analyzed the relationship between patient characteristics, factors associated with Parkinson’s disease (PD), and physical activity level of individuals affected by the disease. Forty-six volunteers with mild-to-moderate idiopathic PD were assessed using sections II/III of the Unified Parkinson’s Disease Rating Scale and their motor functions were classified according to the modified Hoehn and Yahr (HY) scale. Data such as age, disease duration, the Human Activity Profile (HAP), the Fatigue Severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
4
0
5
Order By: Relevance
“…Patients who experience higher levels of fatigue are less physically active in their daily lives 15 . Nonetheless, this symptom was not able to predict the level of physical activity in two proposed models by Lana, although fatigue was correlated with Human Activity Profile scores 16 . Physical activity, physical function, psychological well-being, and quality of life were reduced in PD patients with greater subjective fatigue 6-8 .…”
Section: Can Fatigue Predict Walking Capacity Of Patients With Parkinmentioning
confidence: 80%
See 1 more Smart Citation
“…Patients who experience higher levels of fatigue are less physically active in their daily lives 15 . Nonetheless, this symptom was not able to predict the level of physical activity in two proposed models by Lana, although fatigue was correlated with Human Activity Profile scores 16 . Physical activity, physical function, psychological well-being, and quality of life were reduced in PD patients with greater subjective fatigue 6-8 .…”
Section: Can Fatigue Predict Walking Capacity Of Patients With Parkinmentioning
confidence: 80%
“…Although fatigue is an important symptom in PD, only few studies have assessed its association with mobility, walking capacity, and physical activity in patients with PD [14][15][16][17][18] . Some studies have shown an association between fatigue severity and self-reported leisure activity, frequency of vigorous physical activity, and time spent moving 14 .…”
Section: Can Fatigue Predict Walking Capacity Of Patients With Parkinmentioning
confidence: 99%
“…160 The DA replacement therapy remains an effective treatment for symptomatic control of the motor aspects of the disease, although efficacy declines with disease progression. 161 There is conflicting evidence regarding the efficacy of l-DOPA (a first-line drug used in the treatment of PD) in treating fatigue, 20,162 although it may be alleviated using methylphenidate (DA and noradrenaline reuptake inhibitor). 163 l-DOPA-treated PD patients sometimes report reduced exercise capacity and fatigue onset.…”
Section: Fatigue and Msmentioning
confidence: 99%
“…The combination of motor limitations in PD can seriously compromise the ability to perform tasks such as walking, writing, turning and moving in bed 3 . The progression of the disease is related to increasing deficits and ensuing deterioration of physical parameters, which may contribute to a sedentary lifestyle and reduced physical capacity, resulting in functional dependence of patients 4 .…”
Section: Introductionmentioning
confidence: 99%